The world Hitler never made : alternate history and the memory of Nazism - Rosenfeld, Gavriel D. 1967- (Cambridge University Press, 2005)
Great Britain defeated : between resistance and collaboration -- The United States and the dilemmas of military intervention -- Germany's wartime triumph : from dystopia to normalcy -- Other nations : a dissenting view -- The fugitive Führer and the search for justice -- The world without Hitler : better or worse? -- Hypothetical holocausts and the mistrust of memory